Cultural Interface in Action: A Case Study of Philippine Indigenous Educational Policy - Giselle Lugo Miole (IAFOR Journal of Education)
This study explores the development and implementation of the Indigenous Peoples’ Education (IPEd) policy in the Philippines, which institutionalizes the practice of cultural interface by combining Indigenous and non-Indigenous knowledge systems in the Philippine curriculum. Using actor-centered institutionalism as an analytical framework, this study investigates the motivations and processes behind the Philippine Government’s strategy of employing an interfacing model in policy and curriculum development. Through in-depth expert interviews and policy documents analysis, this study provides a comprehensive understanding of IPEd’s development and stakeholder involvement. The findings reveal that IPEd shifted from assimilationist approaches to an interface model of education, recognizing Indigenous peoples’ representation and rights to education, and participation in national policy development. The implementation of the IPEd policy necessitates continuous dialogue and collaboration between the Indigenous communities and the state, emphasizing rights-based approach to ensure meaningful inclusion of Indigenous knowledge systems. This study contributes to the ongoing agenda of inclusive education for Indigenous peoples at the national policy level.